Kur’an’a göre taassup - Temel, Ahmet Vefa (My University, 2005)
Kur'ân'a Göre Taassup adlı araştırmamızda Kur'ân'ın taassuba bakışı ele alınmıştır. Bundan dolayı bu araştırma, bir konulu tefsir çalışmasıdır. Çalışmamız giriş ve beş bölümden oluşmaktadır. Giriş kısmında konunun önemi, araştırmada izlenecek metotlar ve istifade edilen kaynaklar ele alınmıştır. Birinci bölümde ise taassubun anlamı, kapsamı ve çeşitleri ile taassupla anlam ilişkisi olan kavramlar etimolojik açıdan ele alınarak açıklanmıştır. İkinci bölümde taassubun öznesi olan insanın; yaratılışı, özgürlük ve sorumluluğu ile olumlu ve olumsuz nitelikleri üzerinde durulmuştur. Üçüncü bölümde de Kur'ân'ın taassuba bakışı ve Kur'ân'a göre mutaassıpların özellikleri hakkında bilgi verilmiştir. Dördüncü bölümde ise taassubu oluşturan psikolojik ve sosyolojik sebepler ele alınmıştır. Beşinci bölümde de taassubun sonuçları ve taassuptan kurtulma yolları üzerinde durulmuştur.

The point of view of Koran to fanaticism has been dealt in our search which is called The Fanaticism in the Koran. So this search is a commentary work with subject. Our work consists of introduction and five sections. In the introduction section, the importance of subject, methods in search and bibliography has been dealt. In the first section, the meaning, the comprehension and kinds of fanaticism and also concepts which have meaning relation with fanaticism has been explained dealing in etymological way. In the second section, it has been dwelled on creating, freedom and responsibility and also positive and negative quality of the man who is subject of fanaticism. In the third section, it has been gave information about the point of Koran to the fanaticism and characteristics of fanaticism, according to Koran. In the fourth section, the psychological and sociological causes which constitutes fanaticism. In the fifth section, it has been dwelled on the results of fanaticism and the ways of to be free from fanaticism.
Keywords: Taassup; Tefsir